Biomass Prediction in Tropical Forests: The Canopy Grain Approach - Proisy, Christophe; Barbier, Nicolas; Guéroult, Michael; Pélissier, Raphael; Gastellu-Etchegorry, Jean-Philippe; Grau, Eloi; Couteron, Pierre (IntechOpen, 2012)
None